2021
DOI: 10.1111/petr.13988
|View full text |Cite
|
Sign up to set email alerts
|

Illness perceptions and beliefs about medication: impact on health‐related quality of life in adolescent kidney transplant recipients

Abstract: There are approximately 10,000 children and adolescents living with CKD in the United States, with a prevalence of 124.2 males and 90.6 females per million. 1 Symptoms of CKD include fatigue, swelling, increased urination, decreased concentration, yellowing/ dryness of the skin, and a shorter stature. Effects of CKD include waste buildup, anemia, high blood pressure, and nerve damage. 1 Kidney transplantation is the optimal intervention and a preferable alternative to dialysis treatment; however, organ transpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
0
4
1
Order By: Relevance
“…Prior studies have found that health beliefs are important predictors of individuals’ quality of life, 32–34 while the current study found that quality of life is also a crucial predictor of individuals’ health beliefs. Our study found that participants who were in a low-declining PCS trajectory were more likely to be in a low-stable perceived benefits, perceived barriers, and cues to action trajectory.…”
Section: Discussioncontrasting
confidence: 47%
“…Prior studies have found that health beliefs are important predictors of individuals’ quality of life, 32–34 while the current study found that quality of life is also a crucial predictor of individuals’ health beliefs. Our study found that participants who were in a low-declining PCS trajectory were more likely to be in a low-stable perceived benefits, perceived barriers, and cues to action trajectory.…”
Section: Discussioncontrasting
confidence: 47%
“…While there is an association between receiving a transplant and improved quality of life, findings revealed that recipients can experience poor mental health after transplantation [27][28][29][30][31][32][33][34][35][36]. Anxiety disorders were the most prevalent reported mental health disorders in the literature [27][28][29][30][31][32][33].…”
Section: Psychosocial Needs the Need For Emotional Supportmentioning
confidence: 99%
“…While there is an association between receiving a transplant and improved quality of life, findings revealed that recipients can experience poor mental health after transplantation [27][28][29][30][31][32][33][34][35][36]. Anxiety disorders were the most prevalent reported mental health disorders in the literature [27][28][29][30][31][32][33]. One study reported symptoms in keeping with Post-Traumatic Stress Disorder (PTSD) including nightmares, irritability, and insomnia, and noted the younger the patient the more severe the symptoms [27].…”
Section: Psychosocial Needs the Need For Emotional Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these significant factors are cognitive in nature and may be related to patient beliefs and perceptions about illness and medication. These factors have received support in the pediatric CKD 5 and kidney transplant 6 literature, and are modifiable through implementation of cognitive behavioral intervention strategies. However, active interventions to improve adherence should not be reserved only for patients whose There are several considerations regarding adherence definition and measurement that are worth pondering.…”
Section: Medication Adherence In Adolescent and Young Adult Transplantmentioning
confidence: 99%